2017
DOI: 10.14814/phy2.13251
|View full text |Cite
|
Sign up to set email alerts
|

Local transmural action potential gradients are absent in the isolated, intact dog heart but present in the corresponding coronary-perfused wedge

Abstract: The left ventricular (LV) coronary‐perfused canine wedge preparation is a model commonly used for studying cardiac repolarization. In wedge studies, transmembrane potentials typically are recorded; whereas, extracellular electrical recordings are commonly used in intact hearts. We compared electrically measured activation recovery interval (ARI) patterns in the intact heart with those recorded at the same location in the LV wedge preparation. We also compared electrically recorded and optically obtained ARIs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The limitation of the current study comprises the simplified geometry and simulation scenario of AP propagation, with predefined AP shapes and transmural AP duration heterogeneity as the only baseline APD gradient. The recent studies such as done by Opthof et al and Boukens et al indicated, that in in vivo experiments the transmural gradient is not normally predominant [ 44 , 45 ]. In the work done by Arteyeva et al it was concluded that the T-wave genesis depends on an interaction of several gradients (apex-base, anterior–posterior, RV–LV) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of the current study comprises the simplified geometry and simulation scenario of AP propagation, with predefined AP shapes and transmural AP duration heterogeneity as the only baseline APD gradient. The recent studies such as done by Opthof et al and Boukens et al indicated, that in in vivo experiments the transmural gradient is not normally predominant [ 44 , 45 ]. In the work done by Arteyeva et al it was concluded that the T-wave genesis depends on an interaction of several gradients (apex-base, anterior–posterior, RV–LV) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, no report fully excluded the possibility of two seemingly opposing mechanisms occurring in the same setting. A critical point of debate however remains the fact that the repolarization hypothesis derives its support, not from the true setting occurring in patients, but mainly experimental models including canine ventricular wedge preparations which were previously found to fail in reproducing the same extent of arrhythmogenesis as in intact canine hearts [ 69 , 90 , 91 ]. One of the few clinical studies in support of the repolarization hypothesis, Morita and colleagues showed that in Brugada syndrome patients, leads corresponding to the RVOT consistently showed a longer QT interval of which dispersion was increased by blocking sodium current ( I Na ) with pilsicainide [ 87 , 92 ].…”
Section: Mechanisms Underlying Arrhythmias In Brugada Syndromementioning
confidence: 99%
“…However, mapping studies using arterially perfused left ventricular wedge preparations and intact hearts suggest that transmural repolarization differences do not fully explain T wave genesis (Opthof et al, 2007;Boukens et al, 2015). By comparing electrical and optical mapping of both intact and left ventricular wedge preparation of canine hearts, Boukens et al (2017) demonstrated that electrical gradients from wedge preparations differed from those of intact hearts, implying that findings from wedge preparations may not extrapolate to the whole heart.…”
Section: Cardiac Ventricular Repolarization and The Surface Ecg T Wavementioning
confidence: 97%